2020
DOI: 10.1002/jppr.1697
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of hospital pharmacists and pharmacy technicians towards expanding roles for hospital pharmacy technicians: a cross‐sectional survey

Abstract: Background The “Pharmacy Technician and Assistant Role Redesign within Australian Hospitals Project” outcomes were released in November 2016. Aim To assess pharmacy staff attitudes towards expanded hospital pharmacy technician (HPT) roles in a Victorian metropolitan teaching hospital. Method An electronic questionnaire circulated to all pharmacists, interns and HPTs remained open for 4 weeks during September 2018. Questions focused on three key domains: HPT involvement in final accuracy checking of inpatient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Semi‐structured interviews were conducted, with pharmacists and pharmacy support staff from two hospitals located within South‐East Queensland, to explore key issues identified in the literature 2,9,10 . Pharmacists and pharmacy support staff (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi‐structured interviews were conducted, with pharmacists and pharmacy support staff from two hospitals located within South‐East Queensland, to explore key issues identified in the literature 2,9,10 . Pharmacists and pharmacy support staff (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, New Zealand and Singapore trialled and implemented the pharmacy accuracy checking technicians and pharmacy technician accreditation, which was informed by the UK and US programs 7,8 . Although the Australian setting is similar to these, the only national training framework, Certificate III and IV in pharmacy support services, is deemed inadequate for current hospital pharmacy support staff, with individual organisations developing in‐house training to address these perceived gaps 2,9 . Further, the acceptance and impact of prior efforts to standardise the tasks of Australian support staff, is unknown 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies that examined the expanded role of pharmacy technicians were carried out in settings where these services were offered under the direct supervision of pharmacists. 14,15 The impact of technicians in these roles was measured in terms of freeing up pharmacists’ time to offer clinical pharmacy services. In this study, we assessed health care providers’ attitudes and satisfaction with patient-oriented pharmacy services offered by pharmacy technicians independent of direct pharmacist supervision.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of this hospital’s pharmacy staff conducted before developing the MEdTech role identified that 46% did not support HPTs providing discharge medication education 12 . Key concerns were whether HPTs had the required knowledge to answer questions and the inefficiency of such a role if the HPT had to refer patients to a pharmacist each time they asked a question.…”
Section: Discussionmentioning
confidence: 99%